Secretory leukocyte protease inhibitor promising protective roles in obesity-associated atherosclerosis - Zhong, Qiao-Qing (Exp Biol Med (Maywood), 2016)
Secretory leukocyte protease inhibitor (SLPI), a serine protease inhibitor, which was most commonly examined in mucosal fluids such as saliva, is a versatile molecule and plays non-redundant roles. In addition to its anti-protease activity, SLPI has been shown to express anti-bacterial, anti-viral, anti-fungal, and anti-inflammatory properties as well as participating in innate and adaptive immune responses, most of which has been well documented. Recently, it is reported that SLPI is expressed in adipocytes and adipose tissue where it could play an important feedback role in the resolution of inflammation. Furthermore, circulating SLPI has been shown to correlate with progressive metabolic dysfunction. Moreover, adenoviral gene delivery of elafin and SLPI attenuates nuclear factor-κB-dependent inflammatory responses of human endothelial cells and macrophages to atherogenic stimuli. This review contributes to unraveling the protective role of SLPI in obesity-related atherosclerosis development, and the potential role in preventing arterial plaque rupture.